Comparison of Trichoscopic Features of Alopecia Areata before and after Treatment with Intralesional Steroids: Trichoscopic Features of Alopecia Areata with Intralesional Steroids - Hoor, Shahana; Rafiq, Zahid; Gardezi, Syed Ahmad Ali; Kousar, Humaira (Pakistan Journal of Health Sciences, 2025)
Alopecia Areata is a common form of non-scarring hair loss. The utility of Trichoscopy lies in diagnosis and monitoring therapeutic response in challenging cases. Objectives: To compare the change in frequency of trichoscopic features of Alopecia Areata before and after treatment with intralesional steroids. Methods: This descriptive longitudinal study was carried out in the Department of Dermatology, Sahiwal Teaching Hospital, Sahiwal. Patients between age 18 to 60 of either sex, having Severity of Alopecia Tool (SALT Score) of less than 50 were enrolled. Intralesional triamcinolone acetate (5mg/ml with lignocaine) was infiltrated at a dose of 0.1 ml /cm2 into the dermis. Trichoscopic features were recorded using Heine Delta 30 digital Dermatoscope at baseline and after 12 weeks. Results: Mean age was 28.19 ± 8.54. There was statistically significant decrease in mean of SALT Score before (9.91 ± 6.77) and after (4.94 ± 4.04) treatment. The frequency of black dots, exclamation mark hairs and yellow dots at baseline was 91%, 81% and 23%. After treatment these frequencies reduced significantly to 8%, 7%, and 9% respectively (p-value<0.001). While the proportion of short vellus hair and circle hair at baseline (63%,12%) increased to 99% and 70% after treatment respectively (p-value<0.001). Conclusions: It was concluded that clinical improvement in Alopecia Areata after treatment with intralesional steroids can be demonstrated with disappearance of yellow dots, black dots, exclamation mark hair and appearance of circle and short regrowing hair on Trichoscopy. Thus, highlighting the utility of Trichoscopy as a valuable tool for monitoring therapeutic response in Alopecia Areata.